Impact of Market Competition on Continuity of Care and Hospital Admissions for Asthmatic Children: A Longitudinal Analysis of Nationwide Health Insurance Data 2009-2013 - Cho, Kyoung Hee (PLoS One, 2016)
BACKGROUND: Ambulatory care-sensitive conditions, including asthma, can be managed with timely and effective outpatient care, thereby reducing the need for hospitalization. OBJECTIVE: This study assessed the relationship between market competition, continuity of care (COC), and hospital admissions in asthmatic children according to their health care provider. METHODS: A longitudinal design was employed with a 5-year follow-up period, between 2009 and 2013, under a Korean universal health insurance program. A total of 253 geographical regions were included in the analysis, according to data from the Korean Statistical Office. Data from 9,997 patients, aged ≤ 12 years, were included. We measured the COC over a 5-year period using the Usual Provider Continuity (UPC) index. Random intercept models were calculated to assess the temporal and multilevel relationship between market competition, COC, and hospital admission rate. RESULTS: Of the 9,997 patients, 243 (2.4%) were admitted to the hospital in 2009. In the multilevel regression analysis, as the Herfindahl–Hirschman Index increased by 1,000 points (denoting decreased competitiveness), UPC scores also increased (ß = 0.001; p < 0.0001). In multilevel logistic regression analysis, the adjusted odds ratio (OR) for hospital admissions for individuals with lower COC scores (≥ 2 ambulatory visits and a UPC index score of < 1) was 3.61 (95% CI: 2.98–4.38) relative to the reference group (≥ 2 ambulatory visits and a UPC index score of 1). CONCLUSIONS: Market competition appears to reduce COC; decreased COC was associated with a higher OR for hospital admissions.